Biofuel Policy and Industrial Transition—A Nordic Perspective - Atle Midttun; Knut Myrum Næss; Proadpran Boonprasurd Piccini (Energies, 2019)
The article explores the interplay between policy, technological innovation and market dynamics. It highlights the challenges of combining biofuel policies for ‘greening’ transport with reviving the Nordic forestry industry. We find that strong policy initiatives have triggered a transition to biofuel in the three Nordic countries but have so far given little stimulus to forest-industrial revival. Instead, biofuel has created dynamic change in the petroleum sector, where retailers and refineries have adopted cheap imported biofuel to diversify out of an exclusive reliance on petroleum, leaving forest-based biofuel unable to compete. However, this does not mean that the forestry industry has remained stagnant. We find that parts of the Nordic forestry industry have staged an impressive revival, though one based predominantly on high value products, such as hygiene products and labels, and not on biofuel. We conclude that, while public policy may influence commercial conditions, it does not—in a market economy—dictate the industrial strategy, which is hard to predict, especially when it moves beyond existing sector-boundaries. However, the recent adjustment in biofuel policy, in part a response to ecological critique, may represent a more promising opportunity for forest-industrial participation in the future.